Nordic Childhoods in the Digital Age Insights into Contemporary Research on Communication, Learning and Education - Kumpulainen, Kristiina; Kajamaa, Anu; Erstad, Ola; Mäkitalo, Åsa; Drotner, Kirsten; Jakobsdóttir, Sólveig (Perspectives on Education in the Digital Age, 2022)
"This book adds to the international research literature on contemporary Nordic childhoods in the context of fast-evolving technologies. It draws on the workshop program of the Nordic Research Network on Digital Childhoods funded by the Joint Committee for Nordic research councils in the Humanities and Social Sciences (NOS-HS) during the years 2019-2021. Bringing together researchers from Finland, Norway, Sweden, Denmark and Iceland, the book addresses pressing issues around children's communication, learning and education in the digital age. The volume sheds light on cultural values, educational policies and conceptions of children and childhood, and child-media relationships inherent in Nordic societies. The book argues for the importance of understanding local cultures, values and communication practices that make up contemporary digital childhoods and extends current discourses on children's screen time to bring in new insights about the nature of children's digital engagement. This book will appeal to researchers, graduate students, educators and policy makers in the fields of childhood education, educational technology and communication."